Analisis Kualitas Air Secara Bakteriologis Pada Sarana Penampungan Air Hujan (PAH) di Desa Klumpu Kecamatan Nusa Penida Kabupaten Klungkung - Dwijayanti, Ni Made; Widya Astuti, Ni Putu; Sumadewi, Ni Luh Utari (HIGIENE: Jurnal Kesehatan Lingkungan, 2021)
Rainwater Storage (PAH) by utilizing building roofs is generally an alternative in obtaining clean water sources that require little processing before being used for human purposes. The use of rainwater as an alternative source of water is very potential to be applied in Indonesia because tropical areas have high rainfall. In Klumpu Village, the community mostly uses PAH facilities to meet their daily needs. The purpose of this study was to determine the bacteriological quality of water in rainwater storage facilities (PAH) in Klumpu Village, Nusa Penida, by using a bacteriological laboratory test method by conducting biological and physical examinations and comparing with ministerial health regulations number 32 of 2017 concerning clean water quality requirements. The samples taken were 27 samples of PAH water in Klumpu Village, Nusa Penida District, Klungkung Regency. The results showed that the PAH water quality in terms of physical parameters, the overall results of the sample were odorless, temperature within normal limits, and color with the TCU scale, the results were <1, while the bacteriological PAH water quality did not meet the requirements as clean water quality based on ministerial health regulations number 32 as much as 18 samples. Keywords : Bacteriological, Rainwater Reservoir Tank (PAH), Klumpu Village Nusa Penida